Anisotropic Magnetoresistance of Cobalt Films Prepared by Thermal Evaporation - Yuttanun PANSONG; Chitnarong SIRISATHITKUL (Walailak Journal of Science and Technology, 2011)
Cobalt films on silicon substrates were prepared by thermal evaporation. By evaporating 0.05 g of cobalt for 80-240 s, a thickness from 21.1 to 67.7 nm was obtained with a deposition rate about 0.26-0.32 nm per second. The 29 nm-thick cobalt film exhibited magnetoresistance (MR) ranging from -0.0793% (field perpendicular to the current) to +0.0134% (field parallel to the current) with saturation in a 220 mT magnetic field. This MR was attributed to anisotropic magnetoresistance (AMR) since changing the angle between the field and the current (θ) gave rise to a change in the electrical resistance (Rθ). The results agreed with the theory since the plot between Rθ and cos2θ could be linearly fitted. AMR was not observed in non-ferromagnetic gold films whose resistance was insensitive to the angle between the current and magnetic field.